SOFTWARE SHELL FOR DEVELOPMENT AND IMPLEMENTATION OF OBJECT RATING ASSESSMENT COEFFICIENT METHODS - Alexander Ivanovich Dolgov (Advanced Engineering Research)
The construction and practical application issues of the software shell for the development and implementation of the rating assessment coefficient methods of objects (engineering, organizational, etc.) are considered. The given shell is designed for those users who wish to develop and enrich the computer coefficient techniques by themselves (without professional programmers’ help). First, the program modules to form the software shell are generated. They provide a user with the means for the text and (or) numeric data input in the standard form edit fields meant for the information entry and display. In this case, a hierarchical information model is generated automatically via the software shell means. A data set describing the evaluated object properties, their value interrelations is presented, and output data tables are formed in it. On the basis of the input data, the user program is automatically generated in the form of the software shell additional module.